1995
DOI: 10.1002/bit.260480315
|View full text |Cite
|
Sign up to set email alerts
|

Hybridoma growth and antibody production as a function of cell density and specific growth rate in perfusion culture

Abstract: Steady state metabolic parameters for hybridoma cell line H22 were determined over a wide range of cell densities and specific growth rates in a filtration based homogeneous perfusion reactor. Operating the reactor at perfusion rates of 0.75, 2.0, and 2.9 day(-1)(each at four different specific growth rates), viable cell densities as high as 2 x 10(7) cells/mL were obtained. For the cell line under investigation, the specific monoclonal antibody production rate was found to be a strong function of the viable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 49 publications
7
37
0
Order By: Relevance
“…higher in the higher specific growth rate culture and lower in lower specific growth rate culture. Similar observations have been reported for hybridoma in perfusion culture where it was found that specific glucose consumption and specific lactate production rates are highly correlated to the specific growth rate of the culture (Banik and Heath, 1995). In general, Figures 4.9 to 4.11 shows that caspase activation is correlated to initial cell density, i.e.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…higher in the higher specific growth rate culture and lower in lower specific growth rate culture. Similar observations have been reported for hybridoma in perfusion culture where it was found that specific glucose consumption and specific lactate production rates are highly correlated to the specific growth rate of the culture (Banik and Heath, 1995). In general, Figures 4.9 to 4.11 shows that caspase activation is correlated to initial cell density, i.e.…”
Section: Resultssupporting
confidence: 85%
“…The perfusion rate depends on the type and culture behavior of the cell line, the concentration of nutrients in the feed and the level of toxicity. This mode of operation has been used for the production of monoclonal antibodies (Banik and Heath, 1995;Tang et al, 2007; and recombinant proteins (AlRubeai et al, 1999;Avgerinos et al, 1990). An example of a 500 L industrial perfusion system for monoclonal antibody production by hyridoma is described by (Deo et al, 1996) where the operation continued for 15 to 35 days to achieve commercial production of antibodies with a cell density of >10 x 10 6 cell/mL.…”
Section: Perfusion Culturementioning
confidence: 99%
“…This has been observed for cells cultivated in batch (Ramirez and Mutharasan, 1990), fed-batch (de Tremblay et al, 1993;Robinson et al, 1994), chemostat (Boraston et al, 1984), and perfusion modes (Al-Rubeai et al, 1992;Banik and Heath, 1995;Batt et al, 1990;de la Broise et al, 1991;Johnson et al, 1996;Hansen et al, 1993;Park and Ryu, 1994;Tokashiki and Takamatsu, 1993;Trampler et al, 1994), as well as in cells treated with cell-cycle blocking agents (Al-Rubeai and Emery, 1990;Jayme, 1991;Mercille and Massie, 1998;Oh et al, 1995;Øyaas et al, 1994a,b;Reddy and Miller, 1994;Suzuki and Ollis, 1990;Takahachi et al, 1994). Indeed, specific antibody production has been shown to be cell cycle dependent and optimum in the G 1 and/or G 2 /M phase (Cazzador and Mariani, 1993;Kromenaker and Srienc, 1991;Linardos et al, 1992;Richieri et al, 1991;Suzuki and Ollis, 1989).…”
Section: Introductionmentioning
confidence: 83%
“…1) is a typical feature of lymphoid cells in perfusion culture. This phenomenon has been observed with a variety of hybridoma cell lines in a number of different perfusion systems, such as those based on cross-flow filtration (de la Broise et al, 1991;Banik and Heath, 1995), vortex-flow filtration (Avgerinos et al, 1990;Mercille et al, 1994c), sedimentation (Kitano et al, 1986;Hansen et al, 1993), centrifugation (Johnson et al, 1996;Tokashiki and Tokamatsu, 1993), hollow-fiber cartridges (de la Broise et al, 1992;Park and Ryu, 1994), and more recently, acoustic filtration (Trampler et al, 1994). While it could be argued that these systems were not optimised and that the accumulation of dead cells was linked to hydrodynamic shear stress in the separation or bioreactor systems (Schmid et al, 1992), the results presented here propose a different explanation.…”
Section: Effect Of E1b-19k On Apoptotic Death Kinetics In Perfusion Cmentioning
confidence: 91%
See 1 more Smart Citation